Analisa Yuridis Tentang Legalitas Alat Pembuktian Dalam Pembatalan Sertifikat Hak Milik Dan Kewenangan Badan Peradilan (Studi Kasus Putusan PN Surabaya Nomor 810/Pdt.G/2014/PN.Sby) - Darmawan, Marchelo Ivan; Suryawati, Nany (Wajah Hukum, 2024)
Legal problems in the land sector occur very often, especially in this situation, land is something that has high economic value. This can trigger land disputes between groups of people in wider society. These disputes or conflicts will give color to people's lives where increasing population growth will increase the responsibility for land demand. Land disputes are disputes that are basically included in the civil section unless there are criminal or legal elements to the land dispute or conflict. This research is normative juridical research. The normative juridical method is a research method for legal science which is carried out to research with library and secondary materials to study the types of legal rules and regulations that have a formal character, namely laws, regulations and literature which are filled with theoretical concepts based on legal approaches. invite. Many land issues end up being resolved in state courts. The case discussed in the writing of this article is the SURABAYA District Court Decision No. 810/Pdt.G/2014/PN.Sby which in its decision stated that the Certificate of Ownership in the case did not have the power of proof according to the law and decided to cancel the Deed of Sale and Purchase which was presented in front of Notaries and PPATs, which are the authority of civil judges to cancel deeds of sale and purchase made in front of Notaries and PPATs, however, civil judges cannot cancel certificates as regulated in SEMA No. 10 of 2020, General Civil Affairs/2/SEMA 10 2020